The influence of import substitution on regional positioning in the system of international economic relations - Andreeva, Elena Leonidovna; Ratner, Artem Vitalyevich; Voronkova, Oksana Nikolaevna; Tarasov, Anatoly Grigoryevich (Economy of Regions, 2018)
The purpose of the research is to substantiate what kind of influence the import substitution has on the positioning of different types of regions in the system of international economic relations. The research is focused on two types of regions - the industrial type (the Sverdlovsk region) and the agricultural type (Rostov and Krasnodar regions). The research hypothesis is following: import substitution influences not only the replacement of imported goods by the domestic ones, but also can change regional positioning in the international economic relations system. The authors propose the methodological approach. It examines the regional economy according to three levels: a system of entities engaged in foreign economic activity; a system of the support of import substitution and export orientation in a region; a system of international economic relations. Regional positioning in the system of international economic relations is expressed in manufacture and agriculture exports and imports. Our methodological approach reveals the dependence between manufacture and agriculture exports and imports and the manufacturing and agriculture output, including correlation analysis.. We have offered a technique based on the comparative analysis of the effectiveness of import substitution in two regions’ types applying correlation analysis. The analysis has shown the interrelation of the development processes of domestic manufacturing and agriculture, their export and import in 2005-2016. The import decrease and export increase (after 2014) were mainly due to regional specialization in international division of labour. This demonstrates the results of import substitution. The research results can be used for further development of the strategies of regional international economic activity including such instruments as import substitution and export promotion.